Journalistic curator, a way to rebuild the public space - Díaz Arias, Rafael (Estudios sobre el Mensaje Periodístico, 2015)
The content curation has born to face information overload and as an alternative to automatic selection by the algorithms. This new movement defends filtering selection and characterization of external contents in order to bring order out of information chaos. In this paper it is developed the concept of journalistic curation, its functions and tasks. It begins by adopting in Spanish the terms of curaduría and curador, rejecting the term curation of contents. It is studied the functions of curation and whether this activity can replace journalism. Tasks, tools and products of journalistic curation are developed in the paper. The central question is whether the journalistic curation can reconstruct the public space fragmented into a myriad of conversations. It is concluded that curation is a function that added to the traditional reporting and edition configure the new journalism. Managing institutional, professional and social sources and the interrelationship of professional and social content is a substantial element for the reconstruction of public conversation.